+0  
 
+1
527
2
avatar+314 

2x^2+4x-7=0

 Oct 8, 2017
edited by ISmellGood  Oct 8, 2017
 #1
avatar+98196 
+2

2x^2 + 4x - 7 = 0

 

Add 7 to both sides

 

2x^2 + 4x  =   7       divide through by 2

 

x^2 + 2x  = 7/2 

 

Take (1/2) of the coefficient on x  = (1/2)(2)  = 1

 

Square this  = 1   and add it to both sides

 

x^2 + 2x + 1  =  7/2 + 1        factor the left and simpify the right

 

(x + 1)^2  =   9/2                  take both roots

 

x + 1  =   ±√ [9/2]

 

x + 1  = ±3 /√2        rationalize the denominator on the righr

 

x + 1  =  ±3√2  / 2      subtract 1 from both sides

 

x =  ±3√2  / 2  -  1

 

x = ±3√2  / 2  - 2/2

 

x = [ -2  ± 3√2 ]   / 2

 

 

 

cool cool cool

 Oct 8, 2017
 #2
avatar+17 
+3

- Aiyan

 Oct 8, 2017

35 Online Users

avatar
avatar